The effect of porosity on fragmentation statistics of dynamically loaded ZrO2 ceramics (Fracture and Structural Integrity, 2017)
The effect of load intensity and porous material structure on the fragmentation statistics of ZrO2(MgO)-based ceramics is studied. Cylindrical samples were fragmented under dynamic compression. Experimental data processing showed that the shape of stress-strain curves, the fragment size distribution and distribution of time intervals between the fractoluminiscense impulses depend on the sample porosity and load intensity. The X-ray Computed Tomography (CT) study of porous material structures allowed us to link the fragmentation statistics with pronounced porosity clustering (about 97% of the total pore volume) formed due to sintering.
Keywords: Fragmentation; Ceramic; Crack cluster